Application of the Precepts of Pancasila as an Effort to Strengthen the Pelajar Pancasila Profile in Elementary Schools: Penerapan Sila-sila Pancasila Sebagai Upaya Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Rezania, Vanda; Fihayati, Zuyyina; Hazim; Aryani, Dian Fitra (Procedia of Social Sciences and Humanities, 2022)
The Ministry of Education and Culture is introducing the Pelajar Pancasila Profile to students as a reflection of the embodiment of Indonesian students who have a passion for lifelong learning, have global competence, and behave in accordance with Pancasila values. Therefore, this study aims to: (1) find out how the application of the Pancasila precepts as an effort to strengthen the character of Pancasila students in elementary schools and (2) analyze the resulting impact .The research methodology applied is a literature study so that it can describe the theory, findings , as well as other research materials obtained from reference materials to be used as the basis for research activities which are then useful for developing a framework of thought related to the character of Pancasila Students. The results obtained are the importance of applying and familiarizing the Pancasila precepts in everyday life both at home and at school as an effort to strengthen the character of the Pancasila Student Profile so that it can produce students who behave in accordance with Pancasila values.